Teaching Narrative Text Using RPG (Role Playing Game) in SMPN 2 Purwoasri for the Second Year Students - Fitra Ardiansyah; M. Syaichul Muchyidin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
Role playing game is defined as one of the popular genres of video games being released for computer and video game console system. In some of role playing game, the students can give the main character is name of story. Especially in teaching narrative using RPG, narrative is basically story within this story telling, there are many kinds of narrative comedy, mystery, romance, etc. The topic of RPG related with education has become interesting topic recently. In SMPN2 Purwoasri, the teacher has been done the implementation of teaching writing using RPG since a year ago. The game was conducted to make students more interesting in in teaching writing. In this research, the design used is descriptive qualitative design. The subject of the research is students VIII-F class which consists of 30 students. Concerning the preparation that the teachers have in teaching writing English at SMPN 2 Purwoasri. The teacher should have the syllabus or lesson plan before they teach writing English at SMPN 2 Purwoasri. Concerning about the material that the teachers used syllabus and lesson plan based on the curriculum 2013. The method used was think pair solo. While the media used as brainstorming the idea in writing is RPG Final fantasy. The teachers automatically evaluated the students’ writing English in every meeting the teacher gives evaluation using four aspect those are: grammatical, generic structure, words and spelling and content Key words: narrative text, teaching process, RPG (Role playing game)